DEVELOPMENT OF COORDINATION ABILITIES OF 8–10 YEAR OLD KARATE PLAYERS AT THE STAGE OF INITIAL TRAINING (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the purposeful use of means of development of coordination abilities of 8-10-year-old karateka at the stage of initial training, the manifestation of which is a guarantee of success at the next stages of multi-year training. The purpose of the study is to determine the influence of the proposed method of development of coordination abilities of young karate players 8-10 years old, at the stage of initial training, on the level of preparedness of athletes. The analysis of the obtained results shows that under the influence of the proposed method of development of coordination abilities at the stage of initial training, indicators of physical development are better in the experimental group than in the control group. Statistically significant differences between the control and experimental groups were established according to the Student's test at p
Keywords: karate; coordination abilities; training; methods; means